Europium‐doped GaN(Mg): beyond the limits of the light‐emitting diode. Issue 3 (7th February 2014) - O'Donnell, K. P.; Edwards, P. R.; Kappers, M. J.; Lorenz, K.; Alves, E.; Boćkowski, M.
Abstract: Rare‐earth doped III‐N semiconductors have been studied for decades on account of their possible application in visible light‐emitting diodes (LED) with built‐in utility as red (e.g. Eu), green (Er) and blue (Tm) monochromatic sources (O'Donnell and Dierolf (eds.), Topics in Applied Physics, Vol. 124 (Springer, Dordrecht, 2010) [1]). However, to date, no commercial devices have been introduced on the basis of these materials. Recently, we discovered thermally activated hysteresis in the emission spectrum of p‐type GaN thin films that were co‐doped with Mg and Eu (O'Donnell et al., Proc. ICPS31, Zurich, July 2012 [2]). We have also reported an unexpected Zeeman splitting and induced magnetic moment of Eu 3+ ions in GaN (Kachkanov et al., Scientific Rep.2, 969 (2012) and MRS Proc. 1290–i03–06 (2011) [3, 4]). These findings encourage speculation on taking the study of RE‐doped III‐N beyond the limited goal of improving LED efficiency into the realm of novel magneto‐optic and quantum‐optical devices. In particular we will describe in this presentation the spectroscopy of ion‐implanted and annealed GaN(Mg): Eu samples and the possible exploitation of the Mg acceptor in GaN as a qubit. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)